Hip muscle imbalance in collegiate athletes: Gender differences - Nadler, S. F.; Malanga, G. A.; DePrince, M. L.; Stitik, T. P.; Feinberg, J. H. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Side to side differences in strength of the glutues maxzimus and medius were evaluated in collegiate athletes with and without a history of low back pain (LBP) and/or lower extremity (LE) injury. Two hundred and three athletes were initially asked to report incidence of LBP and/or LE injury requiring treatment in the past year. Using a specially designed dynamometer anchoring station, three consecutive force measures (Ibs) were then acquired for the glutues maximus and medius muscles. The maximum force generated by each of the four muscles was used to calculate a percentage difference between the right and left extensor (%ME) and the right and left abductor (%MA). In non-injured athletes, the left hip extensor, was on average, 8% stronger then the right extensor. The abductor was, on average, 3% stronger on the right side. In female athletes, with LE injuries but no LBP, the right side was 1.6% stronger than the left (i.e. %ME=1.6%). In non-injured females with no LBP the left side was 9.7% stronger than the right side (i.e. 9.7%). The %ME varied 11.3% between groups, which was found to be significantly different (p=.018). In female athlete with LBP, %MA differed by 17.6% between injured and non-injured groups (p=.006). Male athletes regardless of LE injury or LBP, did not show any significant differences in %MA or %ME. The study suggests that female athletes with LBP may compensate differently to lower extremity injury than those female athletes without LBP. Females, in general, also have different responses of the proximal hip musculature in reaction to LE injury and/or LBP as compared to their male counterparts. Proximal hip strength imbalances may be the cause or effect of continued symptoms and/or reoccurrences in the female athlete. An ongoing prospective study is in progress to further evaluate this relationship.